Rowing performance and estimated training load - Messonnier, L.; Aranda-Berthouze, S. E.; Bourdin, M.; Bredel, Y.; Lacour, J.-R. (International Journal of Sports Medicine, 2005)
We related the rowing performance and the associated physiological parameters to the training load as estimated by a questionnaire addressing the mean habitual weekly energy expenditure (MHWEE) of twenty-one international and national level oarsmen. The questionnaire also addressed the energy expenditure during training (EET) sessions classified as low- (EE1), moderate- (EE2), and high-intensity (EE3). To evaluate the physiological capability of the oarsmen, they performed incremental exercise to determine their maximal oxygen uptake (V·O2max) and the V·O2 relative to V·O2max corresponding to the 4 mmol · l-1 blood lactate concentration (V·O24 %). The mean work rate sustained during a 2000-m all-out event on a rowing ergometer was considered as the rowing performance. On average, the rowers spent 16.4 ± 1.0 h · wk-1 in training with 56 ± 3 % of the time spent on the water. EET represented 43.5 ± 1.7 % of MHWEE. Rowing performance and V·O2max were both related to MHWEE and EET. Also, rowing performance was related to EE1, EE2, and EE3. In contrast, V·O24 % was not related to the estimated energy expenditures. These results suggest that rowing performance and V·O2max are related to training load while V·O24 % was not in the present group of highly trained oarsmen.